Characterization of the Hsp40 partner proteins of Plasmodium falciparum Hsp70 - Njunge, James Mwangi (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Human malaria is an economically important disease caused by single-celled parasites of the Plasmodium genus whose biology displays great evolutionary adaptation to both its mammalian host and transmitting vectors. This thesis details the 70 kDa heat shock protein (Hsp70) and J protein chaperone complements in malaria parasites affecting humans, primates and rodents. Heat shock proteins comprise a family of evolutionary conserved and structurally related proteins that play a crucial role in maintaining the structural integrity of proteins during normal and stress conditions. They are considered future therapeutic targets in various cellular systems including Plasmodium falciparum. J proteins (Hsp40) canonically partner with Hsp70s during protein synthesis and folding, trafficking or targeting of proteins for degradation. However, in P. falciparum, these classes of proteins have also been implicated in aiding the active transport of parasite proteins to the erythrocyte cytosol following erythrocyte entry by the parasite. This host-parasite "cross-talk" results in tremendous modifications of the infected erythrocyte, imparting properties that allow it to adhere to the endothelium, preventing splenic clearance. The genome of P. falciparum encodes six Hsp70 homologues and a large number of J proteins that localize to the various intracellular compartments or are exported to the infected erythrocyte cytosol. Understanding the Hsp70-J protein interactions and/or partnerships is an essential step for drug target validation and illumination of parasite biology. A review of these chaperone complements across the Plasmodium species shows that P. falciparum possesses an expanded Hsp70-J protein complement compared to the rodent and primate infecting species. It further highlights how unique the P. falciparum chaperone complement is compared to the other Plasmodium species included in the analysis. In silico analysis showed that the genome of P. falciparum encodes approximately 49 J proteins, 19 of which contain a PEXEL motif that has been implicated in routing proteins to the infected erythrocyte. Most of these PEXEL containing J proteins are unique with no homologues in the human system and are considered as attractive drug targets. Very few of the predicted J proteins in P. falciparum have been experimentally characterized. To this end, cell biological and biochemical approaches were employed to characterize PFB0595w and PFD0462w (Pfj1) J proteins. The uniqueness of Pfj1 and the controversy in literature regarding its localization formed the basis for the experimental work. This is the first study showing that Pfj1 localizes to the mitochondrion in the intraerythrocytic stage of development of P. falciparum and has further proposed PfHsp70-3 as a potential Hsp70 partner. Indeed, attempts to heterologously express and purify Pfj1 for its characterization are described. It is also the first study that details the successful expression and purification of PfHsp70-3. Further, research findings have described for the first time the expression and localization of PFB0595w in the intraerythrocytic stages of P. falciparum development. Based on the cytosolic localization of both PFB0595w and PfHsp70-1, a chaperone "“ cochaperone partnership was proposed that formed the basis for the in vitro experiments. PFB0595w was shown for the first time to stimulate the ATPase activity of PfHsp70-1 pointing to a functional interaction. Preliminary surface plasmon spectroscopy analysis has revealed a potential interaction between PFB0595w and PfHsp70-1 but highlights the need for further related experiments to support the findings. Gel filtration analysis showed that PFB0595w exists as a dimer thereby confirming in silico predictions. Based on these observations, we conclude that PFB0595w may regulate the chaperone activity of PfHsp70-1 in the cytosol while Pfj1 may play a co-chaperoning role for PfHsp70-3 in the mitochondrion. Overall, this data is expected to increase the knowledge of the Hsp70-J protein partnerships in the erythrocytic stage of P. falciparum development, thereby enhancing the understanding of parasite biology.
Keywords: Plasmodium falciparum; Heat shock proteins; Malaria -- Chemotherapy; Protein-protein interactions; Erythrocytes -- Biotechnology; Molecular chaperones; Host-parasite relationships; Mitochondria